Occupant interactions with shading and lighting systems using different control interfaces: A pilot field study. (15th February 2016) - Sadeghi, Seyed Amir; Karava, Panagiota; Konstantzos, Iason; Tzempelikos, Athanasios
Abstract: The paper presents a field study on human interactions with motorized roller shades and dimmable electric lights in private offices of a high performance building. The experimental study was designed to (i) extend the current knowledge of human-building interactions to different and more advanced systems, including intermediate shading positions and light dimming levels, and (ii) reveal behavioral characteristics enabled through side-by-side comparisons of environmental controls ranging from fully automated to fully manual and interfaces with low or high level of accessibility (wall switch, remote controller and web interface). The research methodology includes monitoring of physical variables, actuation and operation states of building systems, as well as online surveys of occupant comfort and perception of environmental variables, their personal characteristics and attributes (non-physical variables). The analyzed datasets provide new insights on the dynamics of interdependent human interactions with shading and electric lighting systems. Higher daylight utilization was observed in offices with easy-to-access controls, which implies less frequent use of electric lights and less energy consumption accordingly. Analysis of occupant satisfaction, in terms of comfort with the amount of light and visual conditions, based on datasets from offices with variable accessibility to shading and lighting control, reveals a strong preference for customized indoor climate, along with a relationship between occupant perception of control and acceptability of a wider range of visual conditions. Highlights: Studied human interactions with motorized roller shades and dimmable electric lights. Evaluated environmental control setups with manual and web interfaces. Investigated lighting conditions and occupant control actions. Examined physical and non-physical variables for describing human interactions. Evaluated the effects on occupant visual comfort and satisfaction.